2018
DOI: 10.5296/emsd.v7i2.11770
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Impact of Traditional Technology of Charcoal Production in Kpaai District-Bong County Liberia

Abstract: Locally produced charcoal through traditional technology is a source of income to the inhabitants of Kpaai district, Bong-County, Liberia and this has invariably contributed significantly to the country Gross Domestic Product. Two sets of questionnaires were designed and administered randomly to eighty seven consumers and fifty five producers representing sample intensity of between 54-68% and 10-10.3% respectively in five communities among the clans of Waytuah and Wotola. Field observation and Interview data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The study also found that charcoal production and firewood production for markets provide higher average annual income for households than other non-crop means of income. Modernizing the process of wood fuel production system reduces environmental pollution while decreasing the risk of wood fuel production More study needed to reduce the damage due to disease and pest in the planation sector while diversifying the number of fast-growing tree species [10]. Households engage in crop production, wood fuel production, livestock production, bamboo production, and formal employment as their sources of livelihood in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that charcoal production and firewood production for markets provide higher average annual income for households than other non-crop means of income. Modernizing the process of wood fuel production system reduces environmental pollution while decreasing the risk of wood fuel production More study needed to reduce the damage due to disease and pest in the planation sector while diversifying the number of fast-growing tree species [10]. Households engage in crop production, wood fuel production, livestock production, bamboo production, and formal employment as their sources of livelihood in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The dispute aggravated by the expansion of tree plantation on productive cropland of which is strongly unsupported by local agricultural experts. The expansion of tree planting on cropland creates a conflict of interest between cropland and tree plantation land [10] so this study tries to seek solutions for harmonizing conflict of interest between farmers and development agents by providing scientific information.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that charcoal production and firewood production for markets provide higher average annual income for households than other non-crop means of income. Modernizing the process of wood fuel production system reduces environmental pollution while decreasing the risk of wood fuel production More study needed to reduce the damage due to disease and pest in the planation sector while diversifying the number of fastgrowing tree species (Oladeji, Ologunwa, & Tonkollie, 2018). Households engage in crop production, wood fuel production, livestock production, bamboo production, and formal employment as their sources of livelihood in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…On LCA basis, production and conversion routes of fossil fuel-based reductants must be compared to renewable ones. Socioeconomic factors are especially important for the biomass and charcoal production in developing countries, in which biomass and charcoal are the main fuels for heating and cooking [62][63][64][65]. While a larger charcoal demand positively affects the economy of the producers [65], low-and middle-income countries rely on affordable and sustainable cooking fuel supply [64].…”
Section: Reductantsmentioning
confidence: 99%